A Novel Two-Component System, Encoded by the sco5282/sco5283 Genes, Affects Streptomyces coelicolor Morphology in Liquid Culture - Arroyo-Pérez, Erick Eligio; González-Cerón, Gabriela; Soberón-Chávez, Gloria; Georgellis, Dimitris; Servín-González, Luis (Frontiers in Microbiology, 2019)
Streptomyces are mycelial bacteria adapted to grow in soil. They have become important producers of biomolecules with medical applications, but their growth in industrial fermenters is challenged by their peculiar morphology in liquid culture: the hyphae tend to clump and grow as large pellets, which are oxygen- and nutrient-limited, grow slowly and present diminished protein production. Here, by implementing an experimental evolution strategy, a S. coelicolor strain, 2L12, with dispersed morphology and reduced pellet size in liquid culture and no defects in either differentiation or secondary metabolism was selected. Genome sequencing revealed a single amino acid substitution in a sensor kinase, Sco5282, of unknown function to be responsible for the morphological changes. Moreover, genetic and biochemical scrutiny identified Sco5283 as the cognate response regulator and demonstrated that the acquired mutation activates this two-component system. Finally, transcriptomic analysis of the mutant strain revealed changes in expression of genes involved in central processes such as glycolysis, gluconeogenesis, stress-signaling pathways, proteins secretion and cell envelope metabolism. Thus a novel two-component system is proposed to play a key role in the control of Streptomyces extracellular metabolism.